Are the neurocognitive deficits associated with 3, 4-methylenedioxymethamphetamine caused by statistical deficits in ecstasy research? A systematic review. (July 2018) - Amoroso, Timothy
There is growing concern that the majority of modern research may be comprised of false findings, which is partly attributed to unacceptable flexibility in data analyses. Here this issue is considered in the literature suggesting that MDMA (3, 4-methylenedioxymethamphetamine) may be associated with neurocognitive deficits. Research suggests that increased exposure to ecstasy is associated with decreased performance on some neuropsychological tests. This claim is supported by the fact that "heavier" users often perform worse than "light" users on neurocognitive tests. However, most studies use different criteria for defining what is considered a "light" or "heavy" ecstasy user. Here the literature was systematically reviewed to compare the criteria used across studies which compare light and heavy ecstasy users. Out of the 19 studies reviewed nine unique points of dichotomization were found. In many cases, heavy users in one study would have been considered light users in another study and vice versa. Most studies ( n  = 11) did not explain how or justify why a particular criterion was chosen. Only eight studies provided justifications for why they chose a particular criterion and the reasons were often misleading. There are many methodological issues which bring into question the validity of research suggesting MDMA is the cause of neurocognitive deficits. Methodologists have demonstrated that it is unacceptably easy for researchers to report significant findings where no relationship exists, which may have been the case in some studies reporting on the neurocognitive deficits found in ecstasy users.